Islamic Religious Education Students' Perceptions on the Utilization of Artificial Intelligence as a Learning Resource in the Digital Era - Indah Widya Jaya Putri Nasution; Asnil Aidah Ritonga; Sahkholid Nasution (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to analyze the perception of Islamic Religious Education students at the State Islamic University of North Sumatra towards the use of Artificial Intelligence as a learning resource. This study uses a qualitative method with a phenomenological type. Data collection techniques used are questionnaires, observations, interviews, and documentation. Furthermore, the data was analyzed using the Miles and Huberman model combined with ATLAS.ti software. The results of this study indicate that; 1) The information provided by Artificial Intelligence is not completely accurate because there are deficiencies in the depth of explanation and the references listed are not completely valid; 2) AI provides ease of access and use in the learning process; 3) The use of AI is considered efficient in terms of time and cost; and 4) Student ethics in using Artificial Intelligence as a learning resource is not yet entirely good, although it shows a positive direction and growing ethical awareness. This study suggests that in the future, Artificial Intelligence developers need to connect Artificial Intelligence systems with scientific repositories, and that their use must be accompanied by strengthening digital literacy and critical attitudes from users.